The Mediating Role of Intellectual Capital in Enhancing Corporate Governance and Financial Efficiency of Islamic Banks - Qadri Usman, Saif; Kateby, Olfa; Shuiby, Ubaidillah (Inovasi Analisis Data, 2024)
Objective; This research aims to explore the mediating role of intellectual capital in improving corporate governance and financial efficiency in Islamic banks. It examines the influences of governance mechanisms board size, board independence, CEO duality, and Shariah compliance on financial performance through the strategic management of intellectual capital.Methods; The paper uses panel data covering Islamic banks to examine the relationships between variable corporate governance, intellectual capital human, structural, and relational capital and financial efficiency using ZEQTA, NII and LTD through regression models. It also aims to provide context by incorporating macroeconomic variables to the study of governance and performance.Results; The results of the analysis, both correlational and explanatory, indicate a significant impact of corporate governance on the utilization of intellectual capital, with positive effects on the efficiency of financial performance. The more significant dimension was human capital efficiency, whereas governance elements including board independence and Shariah boards showcased high positive associations with financial performance. Intellectual capital also mediated the relationship between governance practices and financial performance.Novelty; This study resonates novelty when linking intellectual capital as a mediating factor between corporate governance and financial efficiency within Islamic banks, extending the understanding on internal development of the firms through intangible assets and how they contour the financial performance in the specific institution.Research Implications; The findings highlight the role of suitable governance mechanisms in better leveraging intellectual capital leading to higher financial performance of the Islamic banking sector. Future researchers may build on this framework by examining how relationships differ as regulatory institutions change, technology evolves, or macroeconomic conditions shift.